Student Achievement of Course Learning Goals in an Asynchronous Distance Learning Course Redesigned using Fink’s Taxonomy of Significant Learning - Downing, Molly; Cynthia H. Canan; T’Bony M. Jewell; Diana D. Kang (Online Learning, 2024)
Fink’s Taxonomy of Significant Learning (FTSL) is an instructional strategy that provides an effective framework for (re)designing course learning experiences to achieve student-centered learning goals. Originally developed for in-person courses, little research exists around its application to effectively design distance learning (DL) courses. This study aims to evaluate if the DL community can also utilize FTSL as a strategy for supporting online learners toward achieving significant learning goals. To address this aim, an asynchronous DL general education course for undergraduates was redesigned by applying FTSL during the development of course learning goals, assessments, and learning activities. A deductive, manifest content analysis was conducted to measure achievement of course learning goals across all nine written course assessments (n=40 student participants). Then, learning frequencies were quantified for each category of significant learning. Study findings indicate most student participants engaged in learning experiences related to five of the six categories within Fink’s taxonomy several times throughout the semester, with higher frequencies of learning in categories for application, followed by the human dimension and foundational knowledge, then caring and integration. In conclusion, study findings support that applying FTSL during the course (re)design process also supports online learners toward achieving significant learning goals, with course assessments that include analysis, aesthetic learning, and self-reflection as useful exercises for achieving said goals. Future research can build on this study by evaluating if online learners that achieve significant learning goals also experience long-lasting change relevant to the learner’s life (i.e., engage in a significant learning experience).